The Effect Of The Application Examples Non Examples Learning Model In Science Biology Subjects To Improve The Control Of The Concept Of 7th Grade Students In SMPN 9 Ambon - Parinussa, Lona (Sains Global Institut, 2019)
This research is a classroom action research that aims to determine whether there is an influence on the application of the examples non examples learning model in an effort to improve the mastery of the concepts of VII-3 grade students of SMPN 9 Ambon in learning biology especially on microscope material. The subjects in this study were students of class VII-3, SMP Negeri 9 Ambon with a total of 28 students consisting of 15 male students and 13 female students. The research procedure is a series of stages of research from beginning to end. The CAR procedure consists of 2 cycles with 3 meetings per cycle, according to the level of the problem to be solved and the conditions to be improved. Each cycle consists of four stages as follows: 1) planning; 2) implementing actions; 3) observation and evaluation of actions; and 4) reflection of actions. The data in this study were collected through tests, observations, interviews applying the Examples Non Examples learning model, and discussions between teachers, peers and collaborators to reflect the results of the PTK cycle. The results of the study show that: (1) The model of learning examples non examples can improve the mastery of microscope material in students of class VII-3, SMP Negeri 9 Ambon; (2) Student learning outcomes for microscope material have increased from cycle I to cycle II; (3) Student learning outcomes have increased along with the increase in students' cooperative skills.